Experimental investigation of the current plasma lens in the non-uniform magnetic field - Belan, V.N.; Butenko, V.I.; Ivanov, B.I.; Kiselev, V.A.; Linnik, A.F.; Onishchenko, I.N.; Prishchepov, V.P.; Yegorov, A.M. (Вопросы атомной науки и техники, 1999)
The ion focusing by the uniform (along the radius and length) current lens was investigated elsewhere. In this work the more complicated, strongly non-uniform (in z-direction) case is considered when parameters of the focusing channel (the current channel radius, current density, focusing azimuthal magnetic field) are changed sufficiently on the focusing distance by the external magnetic field. Theoretically the problem is being solved in details in Ref. [4]. In this work the numerical calculations and experimental investigations are presented.